IGF-1R promotes pain-like behavior in rats with myofascial pain syndrome via the PI3K/AKT pathway - Lingwei Zhou; Miao Pei; Tian Qi; Yu Liu; Xiaoyue Li; Xuan Li; Qinghe Chen; Feihong Jin; Shaozhong Yang; Feng Qi (Scientific Reports)
Abstract Myofascial pain syndrome (MPS) is a common chronic pain condition characterized primarily by the presence of myofascial trigger points (MTrPs). While the insulin-like growth factor-1 receptor (IGF-1R) is known to be upregulated in injured muscles and implicated in orofacial neuropathic pain, its role in the peripheral mechanisms underlying MTrPs remains poorly understood. In this study, we aimed to investigate the expression of IGF-1R in MTrPs and explore the molecular mechanisms by which IGF-1R activation induces pain-like behavior in a rat model of MTrPs. We used Sprague-Dawley rats to assess IGF-1R signaling, measuring pain-like behaviors with the Randall-Selitto test. Muscle tissue morphology was examined using hematoxylin and eosin (HE) staining, while IGF-1R-related proteins were quantified through immunohistochemistry (IHC) and Western blot (WB) analysis. Our results showed that IGF-1R expression is significantly elevated in the muscle tissue of rats with MTrPs, with this upregulation correlating positively with the hyperalgesia. Furthermore, activation of IGF-1R was found to induce pain-like behavior via the phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway. Notably, inhibition of PI3K/AKT reversed the pain-like behaviors triggered by IGF-1R activation. These findings suggest that the increased expression of IGF-1R and subsequent activation of the PI3K/AKT/mTOR pathway may contribute to heightened nociception in MTrPs, offering new insights into the molecular mechanisms underlying MPS and potential targets for therapeutic intervention.